Mekanisme Peralihan Sengketa dari Arbitrase ke Litigasi dan Akibat Hukumnya (Studi Kasus Putusan Nomor 425 B/Pdt.Sus-Arbt/2016 antara PT Sea World Indonesia dan PT Pembangunan Jaya Ancol) - Sundari Arum Kusumawati; Abdul Rahman Prakoso; Putri Indriyani (Jurnal Hukum Lex Generalis, 2025)
This study examines the mechanism of dispute resolution transition from arbitration to litigation and its legal consequences through a case study of Supreme Court Decision No. 425 B/Pdt.Sus-Arbt/2016 between PT Sea World Indonesia and PT Pembangunan Jaya Ancol. The dispute originated from a Build-Operate-Transfer (BOT) agreement that led to differing interpretations regarding the right to extend the management contract. The findings indicate that the shift from arbitration to litigation is permissible when procedural violations or breaches of legal principles occur, as regulated in Law No. 30 of 1999. The legal consequences include the loss of the arbitral award’s executorial power and the emergence of legal uncertainty for the parties involved.